Climatic and evolutionary contexts are required to infer plant life history strategies from functional traits at a global scale. (27th February 2021) - Kelly, Ruth; Healy, Kevin; Anand, Madhur; Baudraz, Maude E. A.; Bahn, Michael; Cerabolini, Bruno E. L.; Cornelissen, Johannes H. C.; Dwyer, John M.; Jackson, Andrew L.; Kattge, Jens; Niinemets, Ülo; Penuelas, Josep; et al.
Abstract: Life history strategies are fundamental to the ecology and evolution of organisms and are important for understanding extinction risk and responses to global change. Using global datasets and a multiple response modelling framework we show that trait‐climate interactions are associated with life history strategies for a diverse range of plant species at the global scale. Our modelling framework informs our understanding of trade‐offs and positive correlations between elements of life history after accounting for environmental context and evolutionary and trait‐based constraints. Interactions between plant traits and climatic context were needed to explain variation in age at maturity, distribution of mortality across the lifespan and generation times of species. Mean age at maturity and the distribution of mortality across plants' lifespan were under evolutionary constraints. These findings provide empirical support for the theoretical expectation that climatic context is key to understanding trait to life history relationships globally. Abstract : Life history strategies are fundamental to the ecology and evolution of organisms and are important for understanding extinction risk and responses to global change. Using global datasets and a multiple response modelling framework we show that the relationship between plant traits and life history strategies depend on climatic and evolutionary contexts, for a diverse range of species at the global scale.